Renormalization and symmetries in quantum field theory - Liu, Zheng (2014)
Divergence arises in calculating some Feynman diagrams representing the scattering amplitudes in quantum field theory. To manage and eliminate the divergence and produce finite results, the renormalization theory was developed. Symmetry plays a crucial role in renormalization. In this thesis, a direct investigation of the symmetry properties (in particular, the Lorentz and gauge symmetries) was performed in the context of quantum electrodynamics (QED). It turns out that these symmetries impose sufficient constraints to the divergence structure to make QED renormalizable. This investigation provides an alternative proof of the renormalizability of QED.